The Influence of the Time Factor and Marital Status on the Quality of Life of Patients After Kidney Transplantation in Uzbekistan - Dilnoza Usmanova; Ulugbek Alimov; Botir Daminov; Aziz Ibragimov (International Journal of Biomedicine, 2024)
Background: Currently, compared to program hemodialysis and peritoneal dialysis, kidney transplantation is considered to be the preferred method of renal replacement therapy in patients with end-stage chronic kidney disease (CKD) in terms of patient survival and improvement in their quality of life (QOL). This study aimed to investigate the influence of the post-transplantation period and marital status on the health-related QOL of patients with CKD who underwent kidney transplantation. Methods and Results: A cross-sectional study was conducted among 78 patients who had received a kidney transplant from living related donors in the Republican Specialized Scientific and Practical Medical Center for Nephrology and Kidney Transplantation between January and April 2022. Kidney transplant recipients (KTRs) were divided into four groups depending on the time after kidney transplantation: 3, 6, 12 months, and 2 years or more after surgery. The study used 2 questionnaires. The first included questions about the sociodemographic data of patients; the second was the standardized health-related QOL questionnaire SF-36. This study of the QOL of KTRs, residents of the Republic of Uzbekistan, showed an improvement in most scales of physical and mental health components 12 months and 2 years or more after kidney transplantation. On the scales of physical and mental health components, unmarried KTRs had a higher self-assessment of QOL than married KTRs, and among married KTRs, those with children had higher QOL indicators. Conclusion: Clarifying how the time after kidney transplantation and individual sociodemographic and medical factors influence QOL indicators requires further research (including longitudinal studies) in a wider КTR population.